Caenorhabditis elegans as an in vivo model to assess fucoidan bioactivity preventing Helicobacter pylori infection. Issue 5 (12th May 2020) - Palacios-Gorba, Carla; Pina, Raquel; Tortajada-Girbés, Miguel; Jiménez-Belenguer, Ana; Siguemoto, Érica; Ferrús, Maria Antonia; Rodrigo, Dolores; Pina-Pérez, Maria Consuelo
Abstract : Fucoidan effectively reduces H. pylori infection. Abstract : Currently, Helicobacter pylori is the unique biological carcinogenic agent. The search for antimicrobial alternatives to antibiotics against this pathogen has been categorized as a priority due to the drastic failure associated with current applied antibiotic therapy. The present study assessed the bioactive antimicrobial capability of fucoidan ("Generally Recognized as Safe" approval – European Commission December 2017) from different species of Phaeophyceae algae ( Fucus vesiculosus, Undaria pinnatifida, Macrocystis pyrifera ) against H. pylori . All the studied fucoidans showed bacteriostatic and bactericidal effects at the studied concentrations [5–100] μg ml −1 and exposure times [0–7 days]. The most effective anti- H. pylori fucoidan was validated in Caenorhabditis elegans as an in vivo model. C. elegans feed was supplemented with Undaria pinnatifida [0–100] μg ml −1 fucoidan, resulting in a significant improvement in lifespan, lowered H. pylori concentration in the digestive tract, and increased egg-laying pattern. New research lines proposing this compound as an active agent in nutraceutical and preventive novel therapies should be opened.